PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP PENGUNGKAPAN SUKARELA DENGAN EFEKTIVITAS KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Pratiwi Nurul Aini; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of managerial ownership on voluntary disclosure with audit committee effectiveness as a moderating variable. An audit committee effectiveness is embedded in independence and expertise of audit committee. Firm size used as control variable.The population used in this study is non-financial companies listed on the Indonesia Stock Exchange in 2013 with a total sample of 84 companies. The sampling method used in this study is purposive sampling. The data used is secondary data that are annual report in 2013. This study uses the technique of multiple linear regression analysis.The empirical result of this study show that managerial ownership have positively sifnificant influenced on voluntary disclosure. Managerial ownership moderated by independence and expertise of audit committee shows higher voluntary disclosure.